2021
DOI: 10.1016/j.compbiomed.2021.104429
|View full text |Cite
|
Sign up to set email alerts
|

The incremental burden of invasive pneumococcal disease associated with a decline in childhood vaccination using a dynamic transmission model in Japan: A secondary impact of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disrupted childhood vaccinations, including pneumococcal conjugate vaccine (PCV). Evaluating the possible impact on the invasive pneumococcal disease (IPD) incidence associated with a decline in childhood pneumococcal vaccination is important to advocate the PCV programs. Using a deterministic, dynamic transmission model, the differential incidence and burden of IPD in children younger than 5 years in Japan were estimated between the rapid vaccination recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…39,57 Also, Kitano et al warned about the consequences of a decline in Hib and pneumococcal conjugate vaccine and projected an increase in the incidence of Hib and invasive pneumococcal disease (IPD) and the related burden of the disease if the decline in vaccination persists during the pandemic. 42,43 While most of our studies reported disruptions in routine pediatric vaccination schedules, some countries sustained their immunization program via catch-up strategies, only facing brief periods of decline in immunization rate. In the Republic of Korea, the pediatric vaccination program remained sustained due to the high-powered national vaccination program and minimal cost of vaccination.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…39,57 Also, Kitano et al warned about the consequences of a decline in Hib and pneumococcal conjugate vaccine and projected an increase in the incidence of Hib and invasive pneumococcal disease (IPD) and the related burden of the disease if the decline in vaccination persists during the pandemic. 42,43 While most of our studies reported disruptions in routine pediatric vaccination schedules, some countries sustained their immunization program via catch-up strategies, only facing brief periods of decline in immunization rate. In the Republic of Korea, the pediatric vaccination program remained sustained due to the high-powered national vaccination program and minimal cost of vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the emergence of measles outbreaks is not unimaginable, as experienced before in not highly vaccinated populations 39,57 . Also, Kitano et al warned about the consequences of a decline in Hib and pneumococcal conjugate vaccine and projected an increase in the incidence of Hib and invasive pneumococcal disease (IPD) and the related burden of the disease if the decline in vaccination persists during the pandemic 42,43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we did not have such data. In Japan, pneumococcal vaccine use decreased yet invasive pneumococcal disease in children was lower during versus COVID-19 due to containment measures 21…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine coverage rates have not had a reducing trend in recent years [ 39 ]. Of note, a new method to estimate the number of cases with influenza has been applied since 2018 [ 40 ]. While this study followed the suggestion by Ministry of Health, Labour and Welfare to adjust the annual number in 2017 or before so the number is estimated with the same method throughout the study period [ 40 ], a continuous monitoring the reported number and the estimated number is crucial to find the best way to estimated the number of cases with influenza.…”
Section: Discussionmentioning
confidence: 99%